2021
DOI: 10.1108/maj-12-2019-2506
|View full text |Cite
|
Sign up to set email alerts
|

Mandatory partner rotation, audit timeliness and audit pricing

Abstract: Purpose The purpose of this study is to provide further evidence on the ongoing debate on the costs and benefits of mandatory audit partner rotation (MPR). Specifically, this study examines how MPR simultaneously affects audit reporting lag (ARL) and audit fees (AFs). Design/methodology/approach A simultaneous approach was adopted to further shed light on the findings currently documented by this line of research. Findings Using Australian data, it was found that MPRs increase AFs but do not affect ARL sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
1
7
0
2
Order By: Relevance
“…Using Australian data, Ferguson et al (2019) examine the association between audit reporting lag and audit partner rotation and find a positive association between audit reporting lag and audit partner rotation for the firms being charged higher audit cost. Azizkhani et al (2021), also using Australian data, examine whether mandatory partner rotation simultaneously affects audit reporting lag and audit cost. They found that audit partner rotation increases audit cost but does not affect audit reporting lag in the year of rotation.…”
Section: H1mentioning
confidence: 99%
“…Using Australian data, Ferguson et al (2019) examine the association between audit reporting lag and audit partner rotation and find a positive association between audit reporting lag and audit partner rotation for the firms being charged higher audit cost. Azizkhani et al (2021), also using Australian data, examine whether mandatory partner rotation simultaneously affects audit reporting lag and audit cost. They found that audit partner rotation increases audit cost but does not affect audit reporting lag in the year of rotation.…”
Section: H1mentioning
confidence: 99%
“…The remaining variables in the primary model (Equation 4) are conventional explanatory variables utilized in previous studies to explain corporate disclosure quality, such as readability and audit research (Azizkhani et al , 2021; Hesarzadeh et al , 2020; Hesarzadeh and Rajabalizadeh, 2019; Oradi and Izadi, 2020; MohammadRezaei and Mohd-Saleh, 2018).…”
Section: Sample and Research Designmentioning
confidence: 99%
“…Firm complexity and risk are controlled by incorporating variables such as restated financial statements ( Rest ), institutional ownership ( InstOwn ), total accruals ( Accruals ), leverage calculated as total debt divided by total assets ( Lev ), operating cash flow divided by total assets ( Ocf ), the natural logarithm of total sales ( LnSale ), the current ratio ( Curr ), loss indicator ( Loss ), the natural logarithm of the number of business segments ( Segment ), Altman's Z-score ( Altz ) and client's age ( LnAge ). For instance, auditing clients who are highly leveraged, more complex (indicated by the number of subsidiaries) or incur losses typically requires more time; thus, reporting lags are expected to be longer and higher audit fees are likely to be charged (Azizkhani et al , 2021). Total accruals are expected to be higher for firms in growth stages (aged firms) than those in stagnant stages (Anthony and Ramesh, 1992; MohammadRezaei et al , 2018).…”
Section: Sample and Research Designmentioning
confidence: 99%
“…Penelitian tentang pengaruh tenur audit dan rotasi auditor terhadap kualitas audit masih mendapatkan hasil yang tidak konsisten (Gipper et al, 2021), Seperti penelitian yang dilakukan oleh Damanhuri & Putra (2020) dan Sari et al (2019) dengan menggunakan proksi opini audit, menemukan bahwa tenur audit memberi pengaruh yang berbeda terhadap kecenderungan pemberian opini audit. Penelitian terkait manfaat penerapan rotasi mandatori auditor sejauh ini juga masih diperdebatkan (Azizkhani et al, 2021), seperti penelitian Kuang et al (2020) dengan proksi restatement, memperoleh hasil yang berbeda dengan penelitian Gipper et al (2021).…”
Section: Pendahuluanunclassified
“…Penelitian tentang manfaat penerapan rotasi mandatori auditor hingga saat ini masih diperdebatkan dan memperoleh hasil tidak konklusif (Azizkhani et al, 2021), seperti penelitian oleh Horton et al (2020) menemukan bahwa rotasi mandatori berpengaruh pada peningkatan kualitas audit yang ditandai dengan peningkatan kualitas akrual. Sedangkan penelitian Kuang et al (2020) membuktikan bahwa material misstatement lebih sering terjadi pada laporan keuangan setelah rotasi mandatori, sehingga pengaruh rotasi mandatori menyebabkan penurunan kualitas audit.…”
Section: Pendahuluanunclassified